Kecenderungan Pengembangan Potensi Tanaman Keladi (Colocasia Esculenta) Sebagai Bahan Pangan Alternatif - Kholil, A Yusuf; Khoirunnisa', Ninin; Nugroho, Anung Prasetyo (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2023)
Karangploso Subdistrict is known as having abundant taro commodity products in Malang Regency. However, the average utilization of the taro plant is not optimal, even though there is a large enough land available and has high potential for the development of the caladium plant commodity. Related to the above, the purpose of this research is to find out (a) the application of agribusiness system in the development of taro commodity, (b) the trend level of land area, production and productivity of taro in Karangploso District, Malang Regency. This research was carried out in Karangploso District as the object of the survey which is the development area for the taro plant commodity in Malang Regency. The respondents used were 30 taro farmers in Karangploso sub-district who were selected randomly. Data Analysis includes Qualitative Descriptive Analysis, and Trend Analysis. The results showed that, (a) The application of the concept of agribusiness in general has not run optimally while aspects of human resources in supporting the agribusiness development of taro commodity are quite adequate, (b) The level of trend (Trend) of the development of harvested area and production of taro commodity shows that this commodity has good prospects. that is good for development, but the trend of its development is still relatively small compared to the level of need for taro in the region.Keywords: Taro Plants, Alternative Foodstuffs, TrendsABSTRAKKecamatan Karangploso dikenal sebagai memiliki produk komoditi tanaman keladi yang melimpah di Kabupaten Malang. Namun demikian rata-rata pemanfaatan tanaman keladi belum optimal, padahal tersedia lahan yang cukup luas dan berpotensi tinggi untuk pengembangan komoditi tanaman keladi tersebut. Terkait dengan hal diatas, tujuan penelitian ini adalah untuk mengetahui (a) penerapan sistem agribisnis dalam pengembangan komoditi keladi, (b) tingkat kecenderungan luas lahan, produksi dan produktivitasi keladi di Kecamatan Karangploso, Kabupaten Malang. Penelitian ini dilaksanakan di Kecamatan Karangploso sebagai objek survey yang merupakan daerah pengembangan komoditi tanaman keladi di Kabupaten Malang. Responden yang digunakan sebanyak 30 petani keladi di Kecamatam Karangploso yang dipilih secara acak. Analisis Data meliputi Analisis Deskriptif Kualitatif, dan Analisis Trend. Hasil penelitian menunjukkan bahwa, (a) Penerapan konsep agribisnis pada umumnya belum berjalan secara maksimal sementara aspek sumberdaya manusia dalam mendukung pengembangan agribisnis komoditi keladi cukup memadai, (b) Tingkat kecenderungan (Trend) perkembangan luas panen dan produksi komoditi keladi menunjukkan komoditi tersebut memiliki prospek yang baik untuk dikembangkan, akan tetapi trend perkembangannya masih relatif sedikit dibandingkan dengan tingkat kebutuhan keladi dalam daerah. Kata kunci: Tanaman Keladi, Bahan pangan Alternatif, Kecenderungan.